The legacy of philosophy and education by Ibn Sina: The integration of knowledge and values in Islam - Faishal, Muhammad (Tawazun: Jurnal Pendidikan Islam, 2023)
This study aims to describe the legacy of Ibn Sina about his thoughts in the field of philosophy and the integrity of science associated with values in Islam. The research method used is content analysis, data sources by collecting 30 articles through Google Scholar, the total articles studied amounted to 30 articles philosophy in the period 2022 to 2023. The results of research on the thoughts and legacy of Ibn Sina include, ethics, and education, which forms the basis of a strong understanding of the integration of science and values in Islam, especially in the context of philosophy and education. Ibn Sina is revered for his contributions to logic and science, with his famous work, "Al-Hikmat al-Masyriqiyyah," providing a solid foundation for the development of science and philosophical thought. Based on Ibn Sina’s philosophical thought, Islamic educational institutions can incorporate Qur’anic learning into the curriculum, adopt philosophy learning strategies, ensure educators have a strong understanding of philosophy, improve mental development of learners, and focus on character building and discipline. Abstrak Penelitian ini bertujuan untuk menguraikan warisan Ibnu Sina tentang pemikirannya di bidang filsafat dan keutuhan ilmu yang dihubungkan dengan nilai-nilai dalam Islam. Metode penelitian yang digunakan analisis konten, sumber data dengan mengumpulkan 30 artikel melalui google sarjana, total artikel yang diteliti berjumlah 30 artikel dalam kurun waktu 2022 hingga 2023. Hasil penelitian pemikiran dan warisan Ibnu Sina mencakup filosofi, etika, dan pendidikan, yang dasar membentuk pemahaman yang kuat tentang integrasi ilmu dan nilai-nilai dalam Islam, terutama dalam konteks filsafat dan pendidikan. Ibnu Sina dihormati berkat kontribusinya dalam bidang logika dan ilmu pengetahuan, dengan karya yang terkenal, “Al-Hikmat al-Masyriqiyyah,” yang memberikan dasar yang kokoh bagi perkembangan ilmu pengetahuan dan pemikiran filosofis. Berdasarkan pemikiran filsafat Ibnu Sina, lembaga-lembaga pendidikan Islam dapat memasukkan pembelajaran Alquran ke dalam kurikulum, mengadopsi strategi pembelajaran filsafat, memastikan pendidik memiliki pemahaman filsafat yang kuat, meningkatkan pelatihan mental peserta didik, dan fokus pada pelatihan karakter dan disiplin